2012
DOI: 10.1371/journal.pone.0035079
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Albumin with Markers of Nutritional Status among HIV-Infected and Uninfected Rwandan Women

Abstract: IntroductionThe objectives of this study are to address if and how albumin can be used as an indication of malnutrition in HIV infected and uninfected Africans.MethodsIn 2005, 710 HIV-infected and 226 HIV-uninfected women enrolled in a cohort study. Clinical/demographic parameters, CD4 count, albumin, liver transaminases; anthropometric measurements and Bioelectrical Impedance Analysis (BIA) were performed. Malnutrition outcomes were defined as body mass index (BMI), Fat-free mass index (FFMI) and Fat mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
2
14
2
Order By: Relevance
“…The difference between the groups was statistically significant. Although no correlation was observed between albumin after 6 months and baseline CD4 count in our study, other investigators have observed a positive correlation between albumin and CD4 in HIV patients initiating ARV [32,34,36,37]. The fact that these patients were initiating ARV, indirectly indicate that they were at an advanced stage of the infection (i.e., CD4 counts below 350 cells/µl).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The difference between the groups was statistically significant. Although no correlation was observed between albumin after 6 months and baseline CD4 count in our study, other investigators have observed a positive correlation between albumin and CD4 in HIV patients initiating ARV [32,34,36,37]. The fact that these patients were initiating ARV, indirectly indicate that they were at an advanced stage of the infection (i.e., CD4 counts below 350 cells/µl).…”
Section: Discussioncontrasting
confidence: 74%
“…Dusingize and co-workers observed a positive correlation between albumin and BMI with HIV positive women having CD4 cells/µl below 200 cells/µl [37]. These results suggest that, at an early stage of the HIV infection, albumin levels may be influenced by other clinical manifestations other than nutritional status.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although low sAlb is commonly regarded as a marker of nutritional status, it is poorly associated with other measures of nutritional status in the general population and in PLWH [8,9]. Other causes of low sAlb may include liver disease (decreased synthesis), enhanced turnover resulting from either increased catabolism or enhanced loss of albumin into the urine or intestine [10], or trans-capillary loss due to increased vascular permeability [11].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in patients with HIV this biochemical parameter is not as useful as in non-infected older patients, since it does not consistently predict malnutrition outcomes. This suggests that albumin may measure end stage disease as well as malnutrition and should not be used as a proxy for nutritional status without further study of its association with validated measures [ 6 ].…”
Section: Biochemical Profilementioning
confidence: 99%